AL-SUNAN AL-MA’TSURAH: LIL IMAM MUHAMMAD BIN IDRIS AL-SYAFI’I - Khoiru Amaliya, Niila; Affandi, Abdullah (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2023)
Hadith, as one of the Islamic scientific disciplines, does not miss out on contributing scientific wealth with the birth of works by scholars. The collection of hadiths in books by mukharrij hadiths is a very significant achievement in the Islamic world, both in what is then called primary books -kutubuttis'ah- and secondary ones.One of the heritage works in the field of hadith is the book Al-Sunan al-Ma's\u>rah lil Ima>m Muh}ammad bin Idri>s al-Sya>fi'i. A collection of hadith narrated by a figure from the Islamic jurisprudence school of law. Therefore, this article wishes to recognize this work as an effort to explore the treasures of Islamic scholarship in the field of hadith, especially